Lao PDR Environment Monitor - World Bank (World Bank, Vientiane, 2020)
This Monitor builds on the experiences of other Country Environment Monitors in the region and embraces the key principles articulated by the framework for preparing Country Environmental Analysis initiatives of the Asian Development Bank and the World Bank. The Monitor has three sections. Section 1 reviews trends in natural resources and environmental quality, along with their linkages to poverty. The capacity of Government institutions, policies, legislation and instruments are assessed in Section 2. The environmental challenges confronting the country are analyzed in Section 3. Information has been obtained from a variety of sources, including the Lao Government and Bank publications, academic and scholarly material and personal experience. Several surveys and assessments were undertaken to obtain additional data and insights: (i) A Capacity Assessment was undertaken to assess the effectiveness of the country's institutions regulatory framework; (ii) Public Environmental Expenditures were reviewed to better understand the allocation and trends in environment-related expenditures; (iii) A Survey of Environmental Attitudes was undertaken to assess the perceptions of individuals working in environmental professions in Lao PDR; and (iv) the Poverty-Environment Nexus in Lao PDR was further studied. The results of these surveys and analyses are included in the report.